Touring Pacific Cultures - Alexeyeff, Kalissa; Taylor, John (ANU Press, 2016)
"Tourism is vital to the economies of most Pacific nations and as such is an important site for the meaningful production of shared and disputed cultural values and practices. This is especially the case when tourism intersects with other important arenas for cultural production, both directly and indirectly. Touring Pacific Cultures captures the central importance of tourism to the visual, material and performed cultures of the Pacific region. In this volume, we propose to explore new directions in understanding how culture is defined, produced, experienced and sustained through tourism-related practices across that region. We ask, how is cultural value, ownership, performance and commodification negotiated and experienced in actual lived practice as it moves with people across the Pacific? 'This collection is a welcome addition to tourism studies, or perhaps we should say post- or para-tourism. The essays bring out many facets and experiences too quickly bundled under a single label and focused exclusively on "destinations" visited by "outsiders". Tourism, we see here, actively involves many different populations, societies, and economies, a range of local/global/regional engagements that can be both destructive and creative. Western outsiders aren't the only ones on the move. Unequal power, (neo)colonial exploitation and capitalist commodification are very much part of the picture. But so are desire, adventure, pleasure, cultural reinvention and economic development. The effect, overall, is an attitude of alert, critical ambivalence with respect to a proliferating historical phenomenon. A bumpy and rewarding ride.' - James Clifford, Professor Emeritus, University of California, Santa Cruz"